Perceptions of students in a pedagogy course on environmental issues and pedagogical practice: an analysis based on Grounded Theory (Research, Society and Development, 2020)
This research aimed to investigate the perceptions of undergraduate students in Pedagogy about environmental issues, as well as their relationship with pedagogical practice. The data were obtained through an activity proposed to the academics, when, based on an excerpt from the song “Passarinhos” (Emicida) and two cartoons containing criticisms of man's actions in relation to the environment, they were able to write a critical text reflective on the subject addressed. The results were analyzed in the light of the Grounded Theory (TFD) and pointed out that the academics understand that environmental problems are caused by human actions, that such problems cause harm to fauna and flora (which they consider the environment) and health of people, and that recent events such as the rupture of the mining dam in Brumadinho-MG and the fires in the Amazon are issues that alert and promote reflection on anthropic actions. Also, the research participants consider that children are the hope of an ecologically healthier world and that issues such as environmental issues must be addressed since the Early Years of Elementary Education, awakening in children the critical and transformative sense of attitudes that may decrease future environmental problems.